Artificial Intelligence on ELT in Higher Education: What is Used and Lectures Strategy - Zurniati, Vivi; Astuti, Indri; Burhan, Kristian; Setiawan, Fadli (Fakultas Sastra Universitas Ekasakti, 2024)
This research aims to see what Artificial Intelligence application used by non-English tertiary students in English classroom. The usages of technological application they occasionally use make their task and assignment. And, what strategies English lecturers may use to respond to students assignment created with the help of AI. Research methodology used in this work is descriptive qualitative one by using Participant Action Research (PAR). This research used interview instrument where students answered some questions related to what applications they were used in completing English assignment. Then the researcher made the transcript and drew conclusion from the answers. Based on the result of interview, Google, Chat GPT, and Gemini were frequently used in doing the assignment. Meanwhile, there were 3 strategies of lecturers’ i.e. suppression of academic ethics, using Automatic Article Generator (AAG), and more practice activity. This research can be useful in the ELT field especially lecturer who teaches English to non-English students at State Islamic University. It is undeniable that AI has become part of learning, due to lack of English proficiency, laziness, or limited time the students have. Using AI is useful for them to carry out task effectively and efficiently. This research is focusing on Artificial Intelligence in ELT specifically for lecturer of non-English classroom. In addition, this research is also focused on university students. It is hope that, this research may become an insight for lecturers to respond to e-cheating in ELT classroom of non-English tertiary students.